2021
DOI: 10.3390/microorganisms9122613
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with Multidrug-Resistant Bacteria in the First Week of Life among Hospitalized Preterm Neonates in Serbia: Risk Factors and Outcomes

Abstract: The aim of this prospective cohort study was to determine the prevalence of gut colonization with multidrug-resistant (MDR) bacteria, risk factors for colonization, infection risk, and outcomes among preterm neonates hospitalized at a tertiary-care center in Serbia. During the period from December 2017 to April 2018, 103 neonates were screened for rectal carriage at admission and on the seventh day of life. Characterization of MDR strains was done by conventional microbiology and molecular methods. Out of 61 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Our results agree with those of Teklu et al, 2019 and Kagia et al, 2019 who also noted a high prevalence of the same germ [21,26]. Indeed, K. pneumoniae and E. coli are the Enterobacteriaceae frequently associated with the production of Beta-Lactamases although this resistance mechanism is also described in the genera Pseudomonas, Proteus, Citrobacter, Morganella, Salmonella [27]. In our study, more than 45% of E-ESBL were isolated from neonatal rectal carriage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results agree with those of Teklu et al, 2019 and Kagia et al, 2019 who also noted a high prevalence of the same germ [21,26]. Indeed, K. pneumoniae and E. coli are the Enterobacteriaceae frequently associated with the production of Beta-Lactamases although this resistance mechanism is also described in the genera Pseudomonas, Proteus, Citrobacter, Morganella, Salmonella [27]. In our study, more than 45% of E-ESBL were isolated from neonatal rectal carriage.…”
Section: Discussionsupporting
confidence: 92%
“…Studies conducted in Morocco have shown prevalence of 22.4% at the time of admission of newborns to the neonatal unit and 92.4% during their stay in the unit [13]. Other authors have reported a rate of 77% of rectal carriage E-ESBL in this age group [27]. In addition to the production of ESBLs in Enterobacteriaceae, the predominance of methicillin resistance was noted in 75.6% of Staphylococcus strains, including 61.3% of S. aureus.…”
Section: Discussionmentioning
confidence: 91%
“…In Tanzania (2017-2018), Tunisia (2015), Gabon (2010-2011), and Cambodia (2012), 56%, 28.6%, 45%, and 55% of the hospitalized children were carriers of ESBL-Ent, respectively [64][65][66][67]. In Serbia (2017-2018), gut carriage with ESBL-producing Kp (ESBL-Kp) or ESBL-producing Ec (ESBL-Ec) was recorded in 59% of the hospitalized pre-term neonates; previous hospitalization, delivery by cesarean section, and mechanical ventilation were associated with colonization [68]. In a study from Morocco (2013Morocco ( -2015, up to 59.4% and 12.5% of the neonatal ICU (NICU)-patients were colonized with ESBL-Ent and CPE, respectively [69].…”
Section: Hospital Settingmentioning
confidence: 99%
“…ESBL-producing bacteria are the most widespread MDROs, with 10% of colonized neonates becoming infected [ 42 ]. Further, in addition to cephalosporins, different Enterobacterales species can also share some genetic elements with different patterns susceptible to other antibiotics [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%